Planktonic Relationships! Authentic STEM Connections Through Partnership Between University of Southern California's Marine Researchers and Los Angeles Unified Elementary School Students. Issue 2 (18th September 2020) - Kelly, Kyla J.; Kast, Dieuwertje J.
Plankton here, plankton there, phytoplankton everywhere! This was the messaging behind the pleasantly planktonic programming that sought to introduce fifth grade students to the work of marine and environmental biology researchers at the University of Southern California. A classroom of 29 fifth grade students from Lenicia B. Weemes Elementary toured the research labs on campus. They learned more about how research is conducted at the university level, and what specifically these labs focus on within the study of marine phytoplankton and cnidarians (corals and anemones), which students were able to view under the microscope and in aquariums. These lab tours provided the students with valuable context for conducting scientific research in the real world, bridging the gap between the information they learn in school and where this research data is generated.